1991
DOI: 10.1111/j.1440-6055.1991.tb02189.x
|View full text |Cite
|
Sign up to set email alerts
|

VIABILITY OF POLLEN CARRIED BY APIS MELLIFERA L. TRIGONA CARBONARIA SMITH AND VESPULA GERMANICA (F.) (HYMENOPTERA: APIDAE, VESPIDAE)

Abstract: Antibiotics on the surface of ants inhibit pathogenic microorganisms and significantly lower pollen viability. However, the viability of pollen in contact with the integument of Apis mellifera L. and Vespula germanica (F.) is not significantly lowered. Trigona curbonaria Smith induces some reduction in pollen viability and this may be the effect of resins harvested for nest construction. The disruption of pollen function by T. carbonaria is much less severe than that produced by ants. Differential integurnenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…We suggest two possible explanations for these differences in pollen viability between flies and bees. First pollen viability declines upon direct contact with some insects (Harriss & Beattie, 1991; Richards et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest two possible explanations for these differences in pollen viability between flies and bees. First pollen viability declines upon direct contact with some insects (Harriss & Beattie, 1991; Richards et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest two possible explanations for these differences in pollen viability between flies and bees. First pollen viability declines upon direct contact with some insects (Harriss & Beattie, 1991;Richards et al, 2005). For example, Richards et al (2005) demonstrated that Brassica napus pollen viability was significantly reduced when in contact with the proboscis of the moth Helicoverpa armigera.…”
Section: Discussionmentioning
confidence: 99%
“…Since these social insects live in moist, crowded nests they have developed glands that produce a volatile substance that kills fungal spores. This substance damages the plasma membrane of fungal spores but may also damage pollen , Mesquida & Renard 1989, Harris & Beattie 1991. Similarly, endozoochory is not without its dangers for seeds (Pakerman et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Entomophilous pollen is also affected by compounds that are secreted by the insect carrier (e.g. bees) [224][225][226]. Plants producing orthodox pollen are potentially out-crossing; both out-crossing and self-pollination can occur in these plant species, unless there is a self-incompatibility system in place to prevent self-pollination [227].…”
Section: Pollen Dehydration Presentation and Anther Dehiscence 91 mentioning
confidence: 99%